OP91 Developing A Celtic Connections Regional Health Technology Assessment Alliance. (2019) - Myles, Susan
Abstract : Introduction: The Irish, Scottish and Welsh national Health Technology Assessment (HTA) bodies (Health Information and Quality Authority, Health Technology Assessment Group, Scottish Health Technologies Group, Health Technology Wales) have recently (2018) established a 'Celtic connections' regional HTA alliance on non-medicine technologies. The primary purpose is to add value by realizing potential economies of scale and scope in non-medicine HTA efforts. Methods: A Memorandum of Understanding (MoU) was agreed to: formalize collaboration and partnership working; improve shared understanding of work programs and processes; collaborate on and co-produce evidence reviews of mutual interest; increase both the volume and range of technology topics for which advice is developed in each nation; promote knowledge exchange; and enhance professional and personal development for each agency's staff. Results: Early benefits include: collaboration on one technology topic resulting in the production of bespoke guidance in three countries; an update of a partner's rapid review; identification of a further potential topic collaboration (sacral nerve stimulation); a six month senior staff secondment; and reciprocal observer membership on each country's national committees. Other general benefits have included: reduced duplication of effort; improved quality assurance through 'critical friend' peer review; enhanced access to methodological advice and a broader range of stakeholders; and development of a forum for discussion and peer support. Conclusions: The alliance offers real potential to optimize use of the scarce resources for non-medicine technologies across the three countries and increase evidence review and guidance volume through adapting or co-producing outputs. Longer term benefits are anticipated to include: improved knowledge exchange; advancing skills of staff; building and broadening capacity through shared learning and access to a wider professional peer group; improved staff recruitment and retention; production of joint publications and other modes of dissemination; and increased profile for each country's work.